**Question 11:**

**(a)**

Expand:

*x*(2 +

*y*)

**(b)**

$\begin{array}{l}\text{Express}\frac{5}{6y}-\frac{3x-5}{12y}\text{asasingle}\\ \text{fractioninitssimplestform}\text{.}\end{array}$

*Solution:***(a)**

*x*(2 +

*y*) = 2

*x*+

*xy*

**(b)**

$\begin{array}{l}\frac{5}{6y}-\frac{3x-5}{12y}\\ =\frac{5\times 2}{6y\times 2}-\frac{3x-5}{12y}\\ =\frac{10-\left(3x-5\right)}{12y}\\ =\frac{10-3x+5}{12y}\\ =\frac{15-3x}{12y}\\ =\frac{\overline{)3}\left(5-x\right)}{{\overline{)12}}^{4}y}\\ =\frac{5-x}{4y}\end{array}$